2022
DOI: 10.1016/j.xphs.2021.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation at Site of Insulin Infusion Diminishes Glycemic Control

Abstract: The approximation of euglycemia is the most effective means of preventing diabetic complications, which is achieved through effective insulin delivery. Recent reports indicate that insulin phenolic preservatives, which are found in all commercial insulin formulations, are cytotoxic, pro-inflammatory and induce secondary fibrosis. Therefore, we hypothesize that these preservatives induce an inflammatory response at the site of insulin infusion leading to diminished glycemic control and adverse pharmacokinetic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that IPP-induced inflammation leads to edema in the air pouch tissue of mice following infusion for up to 7 days [ 10 ]. To evaluate the impact of MCs on edema following IPP infusion, total protein in the lavage fluid was quantified following the infusion of either saline or diluent into the air pouch of non-diabetic mice ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have indicated that IPP-induced inflammation leads to edema in the air pouch tissue of mice following infusion for up to 7 days [ 10 ]. To evaluate the impact of MCs on edema following IPP infusion, total protein in the lavage fluid was quantified following the infusion of either saline or diluent into the air pouch of non-diabetic mice ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note is the significantly increased total leukocyte count mainly driven by an increased neutrophil influx at 3 days in the air pouch of non-diabetic control mice ( C57BL/ 6J) ( Figure 2 A,B). This was not repeated at day 7 or in the HSD:CD-1 strains [ 6 , 7 , 8 , 10 , 11 ]. Although, reduced PMN chemotaxis [ 38 ], including the reduced leukocyte recruitment in diabetes patients [ 39 ] compared to that in non-diabetic controls, has been demonstrated, the reduced immune response in IPP-induced leukocyte influx in STZ-induced diabetic C57BL/6 J mice over a 3-day period warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations